Affective Assessment Dynamics in Islamic Education: A Public and Private High School Comparative Study - Muhammad Ridho Ramadhan; Saepul Anwar; Pandu Hyangsewu (Universitas Nurul Jadid, 2026)
This study investigates the dynamics of planning, implementing, and utilizing affective assessments in Islamic Religious Education (IRE) across divergent institutional contexts, addressing the